The Role of Nahdlatul Ulama’ (NU) Diplomacy in Promoting Islam Rahmatan Lil ‘Alamin Exegesis to Strengthen Indonesian State-Religion Concepts: A Study of Gus Dur’s Thought - Basid, Abdul; Fauzan, Moh.; Amrulloh, Amrulloh; Solichin, Mujianto; Nasih, Ahmad Munjin; Ahmed, Bakri Mohamed Bkheet (Journal of Islamic Thought and Civilization, 2024)
This research aims to examine the role of Nahdlatul Ulama’s (NU) diplomacy in spreading the values of Islam Rahmatan Lil ‘Alamin to strengthen the conceptions of state and religion in Indonesia. This study is beneficial in understanding the fundamental religious organization (NU) that can contribute to interfaith and international dialogue and cooperation, support social harmony, and reinforce an inclusive and tolerant national foundation in Indonesia. Therefore, the current study deployed a qualitative research methodology. The analysis was conducted using data collected through a literature review, in-depth interviews with leaders and members of NU, and a content analysis of videos and netizen comments on the NU Online YouTube channel regarding discussions by Gus Dur about the formation of an Islamic state. This study also explores the genealogy of NU, the state and religious conceptions advocated by NU, and the biography and views of Gus Dur on the topic. The findings indicate that NU, through Gus Dur’s thinking and an inclusive diplomatic approach, has actively promoted an interpretation of Islam oriented towards universal values such as justice, peace, and tolerance. NU reflects this by actively promoting Islam Rahmatan Lil ‘Alamin as the foundation for a stronger, pluralistic, and democratic state. The study also examined the polemics of state and religious conceptions that trigger public discussions and explores the NU differences through cross-faith dialogue and understanding.